A Study of the Distance Learning Programme of the University of Maiduguri and Access to Higher Education in Borno State, Nigeria - Abdullahi, John (West African Journal of Open and Flexible Learning, 2017)
The open and distance learning (ODL) programme is being regarded as one of the most practical way through dual mode which Universities across the world are increasingly adopting in order to increase access to Higher Education. This paper studies the distance learning programme of the University of Maiduguri and access to higher education in Borno State, Nigeria. The objectives of the paper were: to examine the enrolment status of the Distance learning programme from 2012/2013 to 2017/2018 academic sessions; to examine the nature of the programme in terms of flexibility of access and to identify the challenges faced in terms of the programme. The research design used is survey research design. The study used both primary and secondary sources of data. The primary data was obtained through self-administered questionnaire to 260 part 1-5 ODL students of the University of Maiduguri and 6 Heads of Department in the University whose programmes are offered through distance learning, 6 e-tutors of the same programmes and 5 heads of Units at the Centre for Distance learning. The secondary data on Centre for Distance Learning students admission for the period of six Academic Sessions (2012/2013, 2013/2014, 2014/2015, 2015/2016, 2016/2017 and 2017/2018) and the total number of students from part one to five for 2017/2018 Academic Session were obtained from office of the Admission officers of the University of Maiduguri. The study found that access to higher education into University of Maiduguri through the distance learning programme increased every academic session as shown in Figures 2 and 3 with 76%. The study further found that the University of Maiduguri distance learning programme is flexible in mode of operation in terms of admission requirements and conduct of semester examinations as shown in Figure 4. However, the study established that one fundamental challenge of the distance learning programme was inadequate trained e-tutors for effective and efficient service delivery as shown in Figure 5. The study concludes that despite the major challenge the University of Maiduguri Open Distance Learning programme has continued to record increase in enrolment thus providing access to University education in Borno State for both residents of the state and even the entire Northeast region and beyond. The study recommends that the Centre for Distance Learning train more e-tutors to fill the present gap. Résumé : Le programme d'enseignement à distance (ED) est considéré comme l'un des moyens les plus pratiques d'améliorer l'accès à l'enseignement supérieur par le biais d'un double mode que les universités du monde entier adoptent de plus en plus souvent. Cet article étudie le programme d'enseignement à distance de l'Université de Maiduguri et l'accès à l'enseignement supérieur dans l'Etat de Borno, Nigeria. Les objectifs du document sont les suivants : examiner l'état des inscriptions au programme d'enseignement à distance de l’année 2012/2013 à 2017/2018 ; examiner la nature du programme en termes de souplesse d'accès et identifier les difficultés rencontrées dans le cadre du programme. Le plan de recherche utilisé est un plan de recherche par sondage. L'étude a utilisé des sources de données primaires et secondaires. Les données primaires ont été obtenues au moyen du questionnaire auto-administré, adressé à 260 étudiants de la première à la cinquième année de l'enseignement à distance de l'Université de Maiduguri et à six (6) chefs de département de l'Université dont les programmes sont domiciliés, 6 formateurs en ligne des mêmes programmes et Cinque (5) directeurs des sous départements du Centre d'enseignement à distance. Les données secondaires sur l’inscription des étudiants du Centre d'enseignement à distance pour la période de six années scolaires (2012/2013, 2013/2014, 2014/2015, 2015/2016, 2016/2017 et 2017/2018) et le nombre total d'étudiants de la première à la cinquième année 2017/2018 ont été obtenues du bureau des responsables des inscriptions de l'Université de Maiduguri. L'analyse a montré que l'accès à l'enseignement supérieur à l'Université de Maiduguri par le biais du programme d'enseignement à distance augmentait chaque année scolaire comme le montrent les figures 2 et 3 avec 76%. L'étude a également montré que le programme d'enseignement à distance de l'Université de Maiduguri est flexible en termes de conditions requises pour l’inscription et le déroulement des examens semestriels, comme le montre la figure 4. Toutefois, l'étude a établi que l'un des défis fondamentaux du programme d'enseignement à distance était le manque de la formation des tuteurs en ligne pour une prestation de services efficace et efficiente, comme le montre la figure 5. L'étude conclut qu'en dépit du défi majeur, le programme d'enseignement à distance de l'Université de Maiduguri a continué de connaitre une augmentation des inscriptions, permettant ainsi aux résidents de l'État de Borno et même de toute la région du nord-est et au-delà d'accéder à l'enseignement universitaire. L'étude recommande que le Centre d'apprentissage à distance forme un plus grand nombre de tuteurs électroniques pour combler la lacune actuelle.